Fruit nutrition garden: A new approach towards Food Security and Diversification - Bons, Harsimrat K (Indian Horticulture, 2021)
Establishment of Fruit Nutrition Garden in an area of 625 square meters (25 m length and 25 m wide) can meet daily requirement of balanced diet apart from getting good quality, fresh and naturally ripened fruits without pesticide residue throughout the year. Important points to be considered while establishing fruit nutrition garden is discussed in this article. In Fruit Nutrition Garden, 21 types of fruit plants can be planted which can prove as new approach for diversification of fruit plants.